ADDRESSING THE CHALLENGES OF COMPETITION AND FICTIONAL PRICING REGULATION: STRATEGIES AND APPROACHES TO FACING PRACTICEDISHONEST BUSINESS - Nida Garnida Fitrianti; Anggun Yolistina; Raden Roro Fatmasari (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Dishonest business practices, including fictitious pricing, have a significant impact on competitive dynamics in the market and threaten the integrity of a healthy market. In overcoming these challenges, cooperation between companies, partnerships with governments, and collaboration with regulatory bodies play a crucial role. Intercompany cooperation enables the exchange of information and experience to combat unfair business practices. Partnerships with governments enable companies to understand and comply with applicable regulations, while collaboration with regulatory bodies strengthens law enforcement. By considering the internal and external factors that influence the successful implementation of anti-corruption strategies, companies can manage them effectively through a holistic and sustainable approach. By collaborating effectively with these stakeholders, companies can build a fairer, more ethical and sustainable business environment that provides maximum benefits for all parties involved.